Disease activity Score 28 in patients with Chikungunya virus infection - SÁ, Angela Beatriz de (2023)
Objective: This study aims to evaluate different parameters for determining the inflammatory activity in patients with Chikungunya. Patients and methods: An observational, cross-sectional, descriptive, and analytical study was con ducted with 56 patients from May 2018 to June 2020. Seven independent variables were evaluated [pain in 28 joints, oedema in 28 joints, erythrocyte sedimentation rate, global health assessment, Disease Ac tivity Score 28 (DAS28), pain in 64 joints and oedema in 64 joints] and analysed with a regression mod el to determine their influence on patient satisfaction (dependent variable). Results: All studied variables had a significant influence on patient satisfaction, especially the DAS28. However, the agreement between patient satisfaction and the DAS28 was poor (kappa = 0.2). Thus, new cut-off points were established for the DAS28. Compared to the traditional cut-off points used in rheumatoid arthritis, the new cut-off points increased the accuracy of the DAS28 from 37.5% to 51.8%. Conclusions: This study contributes to the literature by presenting the DAS28 as a potentially useful instrument in patients with Chikungunya and using cut-off points adjusted for this population. The results can serve as a reference for future studies with larger sample sizes, which would allow more definitive conclusions.